2009
DOI: 10.5216/ree.v9i1.7139
|View full text |Cite
|
Sign up to set email alerts
|

Busca ativa de sintomáticos respiratórios no controle da tuberculose na percepção do Agente Comunitário de Saúde

Abstract: RESUMO A busca de sintomáticos respiratórios (BSR) é uma das prioridades do Programa Nacional de Controle da Tuberculose. Espera-se que esta atividade esteja inserida no cotidiano de trabalho dos Agentes Comunitários de Saúde (ACS), visando a detecção precoce de casos. O objetivo do estudo foi analisar a incorporação da BSR no controle da tuberculose sob a percepção do ACS. A coleta de dados foi realizada através do levantamento de resultados de baciloscopias antes e após a implantação da BSR no Programa de Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
29

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 3 publications
(3 reference statements)
0
15
0
29
Order By: Relevance
“…[10][11][12][15][16] This structured questionnaire involved 19 questions, divided into two sections, as follows:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][15][16] This structured questionnaire involved 19 questions, divided into two sections, as follows:…”
Section: Methodsmentioning
confidence: 99%
“…[6][7][8][9] Despite being one of the objectives of the CHWs' work, only few studies have addressed the role of these workers in the Active Case Finding (ACF); they are faced difficulties in the development of such action, [10][11][12] showing that this requires knowledge beyond the technical aspects and that there is a need to incorporate a broad view of the health-disease process and their determinants in so far as they have a very close relationship with the community. Therefore, the CHWs have an important role in TB control, since their work involves options for expanding the Respiratory Symptoms (RS) access to the healthcare services, leading to early diagnosis and reduction of morbidity and mortality in the community, caused by TB.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that one of the first symptoms of pulmonary TB (5) (cough) initially presented in a milder manner (7,16) and be considered as a consequence of smoking (17) could remove the suspicion of TB or other severe disease among patients, leading them to not feel the need to search care in a health facility. The delay in seeking care among TB patients who consumed alcohol concurs with other studies (5,18) and may be related to poor perception about their health, as well as the lack of habit of seeking medical care.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that sick people that cough have 11 times more chances to look for care late 25 , that is, for some people, coughing does not mean being sick; so, it leads to the delay in the search for a health service 26 .…”
Section: Rev Bras Epidemiol Apr-jun 2015; 18(2): 313-325mentioning
confidence: 99%